METHOD OF DETERMINATION OF 5-METHYL-6-NITRO-7-OXO-1,2,4-TRIAZOLO[1,5-a]PIRIMIDINIDE l-ARGININY - THE ACTIVE COMPONENT OF DRUG «TRIAZID» BY HPLC METHOD - A. V. Baklykov; A. A. Tumashov; S. K. Kotovskaya; E. N. Ulomsky; G. L. Rusinov; V. L. Rusinov; G. A. Artem’ev; D. S. Kopchuk; V. N. Charushin (Разработка и регистрация лекарственных средств)
A procedure for quantitative determination of 5-methyl-6-nitro-7-oxo-1,2,4-triazolo[1,5-a]pirimidinide l -argininy was developed using the HPLC method with UV detection. To achieve the best chromatographic characteristics, it is proposed to use a column with a grafted octadecylsilyl phase 5-100-c18 (EKA, Sweden). The possibility of applying the developed procedure for the technological control of the third stage of the drug «Triazid» preparation was proved by the validation.